3(4m-7)=-21+12m

Simple and best practice solution for 3(4m-7)=-21+12m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4m-7)=-21+12m equation:


Simplifying
3(4m + -7) = -21 + 12m

Reorder the terms:
3(-7 + 4m) = -21 + 12m
(-7 * 3 + 4m * 3) = -21 + 12m
(-21 + 12m) = -21 + 12m

Add '21' to each side of the equation.
-21 + 21 + 12m = -21 + 21 + 12m

Combine like terms: -21 + 21 = 0
0 + 12m = -21 + 21 + 12m
12m = -21 + 21 + 12m

Combine like terms: -21 + 21 = 0
12m = 0 + 12m
12m = 12m

Add '-12m' to each side of the equation.
12m + -12m = 12m + -12m

Combine like terms: 12m + -12m = 0
0 = 12m + -12m

Combine like terms: 12m + -12m = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| -12u-12=-4(3u+3) | | 5(4m-20)=4(5m-25) | | -12u-11=-4(3u+3) | | 16y=13y+45 | | 12=-5h | | Ax+Gy=m | | 47=32+0.75x | | -2m+10=-2(m+5) | | (3-x)(2-x)(1-x)-8=0 | | 5(x+3)=11(2x+7) | | 16x-12=52 | | 7(c+1)=4(c-2) | | 7.2+2(3x-2)=133 | | 115x=460 | | 14+3(x+2)=2-2(x+9) | | 7(c+1)=4(c-8) | | 16+5=7x-7 | | (x-6)(2x+4)=(x+8)(x-3) | | 5a-2b=-19 | | 20x=10x-3 | | 7c+7=4c-8 | | -3n(2n-5)=0.5(-12n+30) | | 8-2c=-16 | | .66q+.08=q+.125 | | 20=3X+X | | rt-2n=7 | | 42-21x+12x=144 | | x+3x-4=36 | | 5-(-1+3)=-1+2(-1-3) | | -x+(-3)=8 | | 2z+6+3z=-34 | | 5(x+1)=40 |

Equations solver categories